"How I became an ethnobotanist" an interview with ERA Associate Editor Dr. Narel Paniagua Zambrana - Ali, Maroof (Ethnobotany Research and Applications, 2022)
An interview with Narel Paniagua-Zambrana, Senior Scientist of the Department of Ethnobotany at the Institute of Botany, Ilia State University, Georgia, Associated Researcher of Herbario Nacional de Bolivia and co-director of Saving Knowledge. Her work focuses on ethnobotanical research and the preservation of traditional knowledge, in the Andes, the Caucasus, and the Himalayas.